Failure assessment of reinforced rock slopes subjected to bolt corrosion considering correlated multiple failure modes. (April 2021) - Fu, Guoyang; Deo, Ravin; Ji, Jian; Kodikara, Jayantha
Abstract: This paper presents a reliability-based methodology for failure assessment of reinforced rock slopes subjected to bolt corrosion. Strength failure of the rock bolt, bond failure between the rock bolt and the grout and bond failure between the rock and the grout are considered and their load effects are treated as stochastic processes. The failure probability of each failure mode was evaluated using first passage probability, in which two auto-correlation functions are considered for the load effect processes. The correlations among failure modes are also considered for system reliability analysis. The application of the proposed methodology is demonstrated by a worked example. Sensitivity analysis is also undertaken to identify most influential parameters on slope failure probability. It is found that the type of auto-correlation functions and the correlation length of the load effect processes significantly affect the failure probability of each individual failure while the correlations among the failure modes considerably influence the system failure probability. It is also found that cohesion and friction angle are most influential on the failure probability for all failure modes while the corrosion model and the initial bond strengths are only influential for the bond failure between the rock bolt and the grout and both bond failures respectively.